Demystifying piped water supply: Formality and informality in (peri)urban water provisioning. (May 2023) - Narain, Vishal; Vij, Sumit; Karpouzoglou, Timos
Water utilities have favoured the modern ideal of piped networks and infrastructure that is reproduced in policies and discourses about achieving ambitious water targets. In this article, using ethnographic insights from an urbanising village of New Delhi called Rawta, we build on work that challenges the myth of formal water as 'piped' water and informal water as 'non-piped' and explore both piped and non-piped water as dynamic and socially negotiated water regimes. We analyse how water regimes are shaped by complex constellations of formal and informal actors, institutions and technological practices. What constitutes piped water supply in Rawta is in fact largely constituted by an elaborate informal network of underground pipes and water pumps laid down to realise very specific local water needs. We explore what this kind of informality means for drinking water supply in rapidly urbanising peripheries.